Pharmacologic therapy of ocular disease - Whitcup, Scott M.; Azar, Dimitri T. (Springer, 2017)
"There have been major advancements in the pharmacologic treatment of eye diseases over the past decade. With newly discovered disease targets and novel approaches to deliver therapeutic compounds to the eye, patients are seeing improved outcomes. Not only are there better treatments for diseases where treatments existed, we now have effective therapy for previously untreatable and blinding eye disorders. This volume will cover the pharmacologic treatment of eye diseases from the front of the eye including eyelids, conjunctiva and cornea all the way back to the retina and optic nerve. The first section of the volume reviews general principles of ocular pharmacology, pharmacokinetics, pharmaceutical sciences, and drug delivery. In addition, the volume provides an up to date guide to the pharmacologic approach to the key eye diseases that threaten sight or ocular function"--Publisher's description.
Keywords: Eye -- Diseases -- Chemotherapy.; elektronické knihy; electronic books